Analisis Kemampuan Berbicara Siswa Melalui Storytelling di MTs Negeri 7 Sleman - Hidayat, Rahmi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to describe and analyse the development of students' speaking skills through the story telling method at MTs Negeri 7 Sleman. This research is qualitative research with data collection techniques sourced from observation, interviews, and documentation. The results of the study show that there are still many students who have difficulty speaking or using the right words to convey ideas. This phenomenon says that teachers in madrassas usually emphasize more on teaching language theory. The teaching of speaking skills in madrassas generally has a lack of quality. In fact, students are still hesitant to express their opinions and are shy when asking questions, indicating that students' speaking skills have not reached their full potential and have not improved. The use of storytelling can be a significant learning tool because it can help teachers manage students' speaking practice procedures. Thus, the strategy of utilizing students to tell stories is useful and provides opportunities for students to listen and understand what they have heard, students can speak fluently, dare to ask, and dare to answer questions.